Prerequisites of Formation of Strategy of the Food Market Development within Import Substitution and Resource-saving Programs (on the Example of St. Petersburg) - S. S. Voronkov (Управленческое консультирование)
This study describes the necessity of strategy’s creation of the food market within the programs of import substitution and resource-saving program.Aim. Show the need to create a strategy for the food market within the programs of importsubstituting and resource-saving programs.Tasks. Analyze the factors that determine the need to formulate a strategy for the development of the food industry within the framework of import substitution and resource-saving programsMethods. The methodological framework used includes general scientific  methods, legislative acts by theRussian Federation, developed federal and targeted programs of theRussian Federation.Results. The factors the need to formulate food market strategy have been identified Considered the current federal and targeted programs implemented in recent years inRussia. The proposals on the formation of the strategy for the development of the food market have been developed. In particular, it should be developed within the framework of a resource-saving program, with mandatory OTSW analysis.